Mechanisms underlying the effects of caloric restriction on hypertension - Ahmad A. Al Attar (17563152) (2022)
Hypertension is a major risk factor for cardiovascular disease (CVD) as well as a major contributor to all-cause mortality and disability worldwide. The pathophysiology of hypertension is highly attributed to a dysfunctional endothelium and vascular remodeling. Despite the wide use of pharmacological therapies that modulate these pathways, a large percentage of patients continue to have uncontrolled hypertension, and the use of non-pharmacological interventions is increasingly investigated. Among these, caloric restriction (CR) appears to be a promising nutritional intervention for the management of hypertension. However, the mechanisms behind this effect are not yet fully understood, although an evolving view supports a significant impact of CR on vascular structure and function, specifically at the level of vascular endothelial cells, vascular smooth muscle cells along with their extracellular matrix (ECM). Accumulating evidence suggests that CR promotes endothelium-dependent vasodilation through activating eNOS and increasing nitric oxide (NO) levels through multiple cascades involving modulation of oxidative stress, autophagy, and inflammation. Indeed, CR diminishes phenotypic shift, and suppresses proliferation and migration of VSMCs via pathways involving NO and mTOR. By regulating transforming growth factor-β and matrix metalloproteinases, CR appears to reduce ECM and collagen deposition in vascular walls. Here, we offer a detailed discussion of how these mechanisms contribute to CR’s influence on reducing blood pressure. Such mechanisms could then provide a valuable foundation on which to base new therapeutic interventions for hypertension. Other Information Published in: Biochemical Pharmacology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bcp.2022.115035